Pengaruh Beban Kerja Fisik dan Beban Kerja Mental Bagian Produksi Terhadap Produktivitas Pekerja Menggunakan Metode CVL dan NASA-TLX di PT. SXX - Putra Firmansyah, Alif; Rushanti Widodo, Silvi (Universitas Kadiri, 2025)
Worker productivity is an important factor in supporting the achievement of company targets, especially in the production sector. However, high physical and mental workloads can reduce productivity and increase the risk of fatigue. This study aims to analyze the effect of physical and mental workloads on worker productivity at PT. SXX. The method used is Cardiovascular Load (CVL) to measure physical workload based on heart rate, and NASA-TLX to assess mental workload based on subjective perceptions of workers on six dimensions of work. Data were obtained through direct measurement and distribution of questionnaires to production workers. The results showed that most workers experienced moderate to heavy physical workloads and high mental workloads. Further analysis revealed a negative correlation between high workloads and worker productivity levels. These findings indicate the need for improvements in the work system and division of tasks in order to create more balanced and productive working conditions in the industrial environment.